Income Analysis Of Micro Small To Medium Enterprises (Umkm) Coffee Processing Center In The District Bantaeng (Newn Case Study Banyorang Tompobulu Anxiety) - Isnataeni (Pustaka Digital Indonesia, 2023)
Study This carried out at the Village Coffee Processing Center Many people namely at IKM Akar Farmers and IKM Kopi Labbo on March 18 2022. Research This aim For know big income effort and analysis appropriateness business at the Village Coffee Processing Center Many people . Method analysis of the data used in study This is with use formula total cost analysis , revenue , profit , and analysis appropriateness business use Benefit/Cost Ratio formula . Research results This show that income based on analysis costs , total costs , revenues , and total profits . Costs for both Root SMIs Labbo Coffee Farmers and SMEs is costs incurred by the perpetrators business For production the coffee business in period 1 month time , fee This consists from cost fixed and costs variable . Total cost is the total total costs incurred at the time production consisting of from cost fixed and costs variable . Furthermore reception is amount mark the rupiah taken into account from all over products sold . _ So For get results whole income at the Village Coffee Processing Center Many people that is with TC-TR formula where TC is total costs and TR is total revenue . From the results calculation appropriateness business can concluded that the Village Coffee Processing Center Many people worthy For executed and developed Again Because the value of the B/C ratio is more big than zero that is of 0.33 for SME Akar Tani and 0.22 for IKM Kopi Labbo.